THE USE OF ARABIC-LANGUAGE CARTOON FILMS AS AUDIO-VISUAL MEDIA IN LEARNING MAHARAH ISTIMA' (LISTENING SKILLS) OF TENTH-GRADE STUDENTS AT PONDOK PESANTREN MODERN DARUSSALAM LANGKAT - Predy Ady Ray Ritonga; Kamalia Kamalia (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study aims to analyze and demonstrate the influence of using Arabic-language cartoon films as audio-visual media in improving the **maharah istima'** (listening skills) of tenth-grade students at Pondok Pesantren Modern Darussalam Langkat. The main problem underlying this research is the students' difficulty in communicating and listening to Arabic, caused by the lack of engaging and interactive audio-visual learning media. By employing a qualitative approach and a naturalistic method, this study observes the learning process to gain an in-depth understanding of the implementation of such media. The results show that Arabic-language cartoon films significantly enhance students' ability to identify vocabulary and expressions, while also fostering greater learning interest. It is expected that this research can provide innovative solutions for educators to make Arabic language learning more effective and enjoyable.